Nursing of a patient with phlebitis treated with Traditional Chinese Medicine collapse stains (中药塌渍治疗静脉炎1例的护理体会) - WANG Jingjing (王晶晶); ZHANG Tingting (张婷婷); ZHOU Jie (周洁) (中西医结合护理)
This paper summarized the nursing measures of a patient with grade 2 phlebitis treated with Traditional Chinese Medicine collapse stains. The nursing assessment, application method and cautions of collapse stains, composition of Chinese herbs, dietary guidance and psychological intervention were reviewed. Through the active intervention of the external treatment of Traditional Chinese Medicine, the level of phlebitis decreased, pain was relieved, and good results were achieved. (本文总结1例中药塌渍治疗静脉炎患者的护理措施和体会, 包括护理评估、中药塌渍操作方法、药方组成、注意事项以及饮食指导、心理干预等护理措施。基于辨证施护理念。通过中药塌渍外治法积极干预, 并辅以相关护理措施, 患者静脉炎症状明显好转, 疼痛减轻。)